Enhancing combat readiness via evidence-based pedagogical innovations in National Guard of Ukraine officer training (Educational Dimension, 2024)
This study examines the effectiveness of innovative pedagogical conditions in enhancing combat readiness among future officers of the National Guard of Ukraine (NGU). Utilising a quasi-experimental design, we implemented and evaluated a set of pedagogical interventions integrating recent combat experience into officer training at the Kyiv Institute of the National Guard of Ukraine. The study involved 74 trainee officers divided into experimental (n=35) and control (n=39) groups. Results demonstrated significant improvements in the experimental group across functional, psychological, and reflective components of combat readiness, with increases of 43%, 25%, and 32%, respectively, in high-level readiness. These findings underscore the importance of rapidly integrating field experiences into military education, offering valuable insights for enhancing officer training in dynamic conflict environments. The study contributes to the broader understanding of adaptive military education strategies and provides a framework for implementing evidence-based training reforms in military institutions globally.
Keywords: combat readiness; military education; experiential learning; National Guard of Ukraine; officer training; combat experience integration; pedagogical conditions